2013
DOI: 10.1371/journal.pone.0062642
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between IGF-IR and ER Induced by E2 and IGF-I

Abstract: Estrogen receptor (ER) is a nuclear receptor and the insulin-like growth factor-I (IGF-I) receptor (IGF-IR) is a transmembrane tyrosine kinase receptor. Estrogen and IGF-I are known to have synergistic effects on the growth of breast cancer cells. Recently, non-nuclear effects of ER have been under investigation. To study the mechanism involved in this process, we have used MCF-7 breast cancer cell lines transfected with IGF-IR anti-sense cDNA (SX13, MCF-7SX13) that resulted in 50% reduction of IGF-IR. In MCF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 31 publications
3
37
0
5
Order By: Relevance
“…Altogether, even if plausible mechanisms have been suggested, and has been supported by experimental studies [41], less is known about the association of the GH-IGF signaling pathway, estrogen and mammographic density. Recently, estrogen and IGF-1 have been observed to have synergistic effects on the growth of breast cancer cells [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Altogether, even if plausible mechanisms have been suggested, and has been supported by experimental studies [41], less is known about the association of the GH-IGF signaling pathway, estrogen and mammographic density. Recently, estrogen and IGF-1 have been observed to have synergistic effects on the growth of breast cancer cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, estrogen and IGF-1 have been observed to have synergistic effects on the growth of breast cancer cells [41]. Moreover, GH regulates the production of IGF-1, and around 99% of circulating IGF-1 is bound to IGFBP-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the test results are consistent with the result of radioimmunoassay and immunocytochemistry (ICC) by other researchers (Surmacz, 2000). The present study also found the expression rate of IGF-IR and SUSD3 in ER-positive breast cancer tissue was significantly higher than that in ER-negative tissue.Our previous studies have shown that IGF-IR has interaction with ER in MCF-7 and NWTB3 breast cancer cell lines, and estrogen can induce the expression IGF-IR (Yu et al, 2013a). However, there is no report about association between SUSD3 and IGF-IR currently.…”
Section: Discussionmentioning
confidence: 96%
“…The 17β-estradiol-ERα complex binds and activates IGF-1R directly. Vice versa, IGF signalling enhances ERα activation in human breast cancer cells by phosphorylation (Yu et al 2013). 17β-estradiol and IGF-1R synergistically enhances S phase entry in breast tumor cells (Yu et al 2013).…”
Section: Introductionmentioning
confidence: 99%